2012
DOI: 10.1097/01.sa.0000414272.81787.47
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Lung Protective Strategy for Organ Donors on Eligibility and Availability of Lungs for Transplantation

Abstract: The current investigators applied nonlinear mathematical tools to HR and RR time series during weaning trials and compared these analyses between successfully weaned patients and those who failed weaning. They found that patients who had successful weaning had a more complex pattern of HR and RR patterns than those who failed. They proposed a model to predict weaning that was more accurate for their group of patients than the conventional model that included rapid shallow breathing index and airway occlusion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 1 publication
0
17
0
2
Order By: Relevance
“…[43][44][45] In this study, the FIO 2 of 0.5 was chosen to maximize the quantity and improve the quality of the donor. In preliminary experiments, a PEEP of 5 cm H 2 O affected hemodynamic stability, so a PEEP at 2 cm H 2 O was chosen.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45] In this study, the FIO 2 of 0.5 was chosen to maximize the quantity and improve the quality of the donor. In preliminary experiments, a PEEP of 5 cm H 2 O affected hemodynamic stability, so a PEEP at 2 cm H 2 O was chosen.…”
Section: Discussionmentioning
confidence: 99%
“…11 Mascia et al demonstrated that a protective lung strategy in patients diagnosed with brain death could hinder the development of lung dysfunction and double the number of lungs available for transplantation. 16 These investigators observed that protective ventilator management alone doubled the rate of lung grafts available for transplant, mainly because PaO 2 /FIO 2 remained the same in the protective group and decreased in the conventional group. The fall in PaO 2 /FIO 2 levels from brain death to organ recovery is one of the main reasons for Evolution of PaO 2 /FIO 2 (relation between arterial oxygen pressure and inspiration oxygen fraction [mm Hg]) in potential lung donors after treatment implementation.…”
Section: Discussionmentioning
confidence: 95%
“…Improvements in lung procurement with donor-management strategies have also been reported by others. 7,16 However, most of these studies have included very strict exclusion criteria that ruled out many potential donors 16 or a young average lung donor age, even o40 years of age. 7 We applied this treatment to all donors with no absolute contraindications for lung donation, which brought our lung donor age close to 50 years (see Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Vergleichbar häufig werden nach Organentnahme die Lungenexplantate zur Transplantation abgelehnt. Schätzungen gehen davon aus, dass deutlich mehr Lungen transplantabel wären [1,42] [1,7,25,43].…”
Section: Pulmonale Intensivtherapieunclassified